2015
DOI: 10.1021/acs.est.5b01208
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterials in Biosolids Inhibit Nodulation, Shift Microbial Community Composition, and Result in Increased Metal Uptake Relative to Bulk/Dissolved Metals

Abstract: We examined the effects of amending soil with biosolids produced from a pilot-scale wastewater treatment plant containing a mixture of metal-based engineered nanomaterials (ENMs) on the growth of Medicago truncatula, its symbiosis with Sinorhizobium meliloti, and on soil microbial community structure. Treatments consisted of soils amended with biosolids generated with (1) Ag, ZnO, and TiO2 ENMs introduced into the influent wastewater (ENM biosolids), (2) AgNO3, Zn(SO4)2, and micron-sized TiO2 (dissolved/bulk m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 39 publications
7
81
0
Order By: Relevance
“…The results reported here add clarification to a recent study by Judy et al (2015) which reported that PLFA biomarkers associated with AMF were significantly reduced and soil microbial communities significantly affected in biosolids-amended soils spiked with ENMs relative to biosolids-amended soils treated with bulk/dissolved metal . In that study, wastewater treatment plant influent was spiked with either Ag, TiO 2 , and ZnO ENMs, spiked with Ag, TiO 2 , and ZnO bulk/dissolved metal, or unamended with metals (control).…”
Section: Tablesupporting
confidence: 85%
“…The results reported here add clarification to a recent study by Judy et al (2015) which reported that PLFA biomarkers associated with AMF were significantly reduced and soil microbial communities significantly affected in biosolids-amended soils spiked with ENMs relative to biosolids-amended soils treated with bulk/dissolved metal . In that study, wastewater treatment plant influent was spiked with either Ag, TiO 2 , and ZnO ENMs, spiked with Ag, TiO 2 , and ZnO bulk/dissolved metal, or unamended with metals (control).…”
Section: Tablesupporting
confidence: 85%
“…Considering that non‐labile transformation end products such as AgCl and Ag 2 S are expected to be stable in the environment and to have relatively low bioavailability (Lombi et al ; Donner et al ; Doolette et al , ), the risk to terrestrial ecosystems posed by Ag NMs would appear to be low, although uncertainties related to longer‐term transformations, dosimetry, are also relevant. This conclusion has been further supported by soil‐based studies demonstrating that Ag 2 S NMs presented minimal hazard to plant–microorganism symbioses (Judy et al , ), crop plants (Doolette et al ; Wang et al ), soil microorganisms (Judy et al ; Doolette et al ; Moore et al ), and soil invertebrates (Starnes et al , ).…”
Section: Bioaccumulation and Toxicity Of Nms To Soil Organismsmentioning
confidence: 85%
“…Judy et al () reported data from a study examining the effects of amending soil with biosolids containing either bulk/dissolved TiO 2 , Ag, and ZnO, nanoparticulate TiO 2 , Ag, and ZnO, or containing no added metals (Chen et al ; Judy et al ). These biosolids were generated using pilot WWTP facilities, and the metal input into the waste streams was subjected to chemical conditions similar to what they would experience in an actual WWTP facility.…”
Section: Bioaccumulation and Toxicity Of Nms To Soil Organismsmentioning
confidence: 99%
“…195, 205, 206 Studies at entire WWTP scales elucidate ENM fates during wastewater treatment, including significant association with biological treatment biomass 201, 207 that becomes biosolids. 76, 208 However, only 50% of biosolids produced in the U.S. are land-applied, and these biosolids are used on less than 1% of agricultural land in the U.S. (http://www.epa.gov/biosolids). Biosolids are land-applied even less in the European Union.…”
Section: What Exposure and Design Considerations Drive Mesocosm Assesmentioning
confidence: 99%